2021
DOI: 10.3389/fpsyg.2021.558690
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Trait Mindfulness, Attention, and Working Memory in Junior School Students Under Different Stressful Situations

Abstract: Attention and working memory are important cognitive functions that affect junior school students’ learning ability and academic performance. This study aimed to explore the relationships among trait mindfulness, attention, and working memory and to explore differences in performance between a high trait mindfulness group and a low one in attention and working memory under different stressful situations. In study 1, 216 junior school students completed the Five Facet Mindfulness Questionnaire (FFMQ), and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
4
14
0
Order By: Relevance
“…Based on prior research in various populations that has linked dispositional mindfulness and executive functioning with enhanced emotional regulation (e.g., Lyvers et al, 2014 ) and reduced distress (e.g., Conversano et al, 2020 ; Stout & Rokke, 2010 ), we expected significant negative correlations between (a) dispositional mindfulness and (b) executive functioning with psychological distress. Further, in accordance with theoretical frameworks that have suggested executive function may be a central skill for dispositional mindfulness ( Hölzel et al, 2011 ; Malinowski, 2013 ) and studies that provided empirical support to these assumptions ( Jaiswal et al, 2018 ; Li et al, 2021 ; Riggs et al., 2015 ), we expected to find significant positive correlations between individual athlete’s executive functioning and dispositional mindfulness.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Based on prior research in various populations that has linked dispositional mindfulness and executive functioning with enhanced emotional regulation (e.g., Lyvers et al, 2014 ) and reduced distress (e.g., Conversano et al, 2020 ; Stout & Rokke, 2010 ), we expected significant negative correlations between (a) dispositional mindfulness and (b) executive functioning with psychological distress. Further, in accordance with theoretical frameworks that have suggested executive function may be a central skill for dispositional mindfulness ( Hölzel et al, 2011 ; Malinowski, 2013 ) and studies that provided empirical support to these assumptions ( Jaiswal et al, 2018 ; Li et al, 2021 ; Riggs et al., 2015 ), we expected to find significant positive correlations between individual athlete’s executive functioning and dispositional mindfulness.…”
Section: Introductionsupporting
confidence: 75%
“…We calculated an a priori sample size estimate for correlational analysis using the pwr package in R (version 1.3–0; Champeley, 2020 ). On the basis of a one-tailed correlation with an assumed effect size of r = .48 ( Li et al, 2021 ; Moreton et al., 2020 ) with α = 0.05 and desired power of 0.80, the estimated required sample size was 25 participants. Based on this estimate, we recruited 30 male Australian football athletes from one semi-professional club based in South Australia as prospective participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have focused on a discrete life stage (ie, childhood, adolescence, or adulthood), [22][23][24][25] whereas others have focused on an educational stage (ie, preschool children, primary school students, or college students). [26][27][28][29] Data reported by Gathercole et al indicated that working memory capacity increases linearly from age 4 to 15 years. [4] In a study of children aged 6 to 12 years, it was found that the digital memory span of primary school students increased as their age (grade) increased.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies on the relationships among spatial working memory, attention, and age have focused on adults; only a few have investigated these relationships in young populations such as children in primary school [19–21] . Some have focused on a discrete life stage (ie, childhood, adolescence, or adulthood), [22–25] whereas others have focused on an educational stage (ie, preschool children, primary school students, or college students) [26–29] . Data reported by Gathercole et al indicated that working memory capacity increases linearly from age 4 to 15 years [4] .…”
Section: Introductionmentioning
confidence: 99%